PENGARUH PERLAKUAN AWAL BASA DAN HIDROLISIS ASAM TERHADAP KADAR GULA REDUKSI AMPAS TEBU [The effect of alkali pretreatment and acid hydrolysis on bagasse-reduced sugar]. - Sutikno Sutikno; Marniza Marniza; Novita Sari (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2015)
ABSTRACTBagasse, solid waste by product of sugar cane industries, contains high lignocellulose consisting of 46.3% cellulose, 23.0% hemicellulose and 19.7% lignin. The bagasse can be converted into bioethanol after pretreating with base and acid and then fermenting with microbes. The objective of this study was to find out the effects of sodium hydroxide pretreatment and sulfuric acid hydrolysis on bagasse reduced sugar content. In this study, there were 2 treatments with 3 replications. The first treatment was submerssion bagasse into 1.0 NaOH solutions at a temperature of 121oC for 15 minutes. The second treatment was concentrations of sulphuric acid (H2SO4) that consisted of 5 levels, i.e. 0 M, 0.05 M, 0.10 M, 0.20 M, and 0.30 M. One and an half grams of dried and ground bagasse was put into 100 mL Erlenmeyer flash and then added with 30 mL 1.0 M NaOH solution. The flash was heated at a temperature of 121oC for 15 minutes. After filtering, the residue was hydrolyzed with H2SO4 solution. The residue as well as 1.5 g dried and ground bagasse without pretreating with NaOH was hydrolyzed with 15 mL H2SO4 at concentrations of 0, 0.05, 0.10, 0.20, and 0.30 M at a temperature of 121oC for 15 minutes. Filtrates of the solutions were taken to analyze their reduced sugar content. Reduced sugar content of the bagasse samples ranged from 0.05 to 4.20 mg/100 mL. The highest reduced sugar content (4.20 ml/mL) was yielded when bagasse was directly, hydrolyzed with 0.05 M H2SO4 at a temperature of 121oC for 15 minutes.Keywords : Bagasse, bioethanol, lignocellulose, sulphuric acid, reducing sugar